Implementasi Manajemen Konflik Dalam Penyelesaian Masalah Pembelajaran Di MI Al Quran Singosari Malang - Akhmad Fakhrur Rozi (Leadership: Jurnal Mahasiswa Manajemen Pendidikan Islam, 2020)
The Teghnologis Graming such a fast and modern in Madrasah Ibtidaiyah Al Quran Singosari Malang was the one of the departement. Either an educational formal and non formal in the islamic boarding school. for answering chace of global the need insight of the word science or heaven. this school the location at Jl ronggowuni candirenggo singosari malang upcoming MI Al Quran the vanture to be school cumate of calm. of need the one methode or conflict of management. the implementation of management to conflict can creat condusife or relationship and culture honour of diversity, can accept critice for of change the honour of another also the creat communication can be opened with to reel a patient.This Reseach was The Qualitatif deeply sharp study cacus. the procedure was taking of data at either observation, interview, and documentation. the analysis data are insed 1. union of data 2. condentation data 3. giving of data 4. verivication. the check original data were credibility and dependability.The goal this research was 1. knowing the implementation conflict of management in MI Al Quran Singosari Malang 2. knowing mandatory head school  deeply implementation conflict of management.The conclution was the management conflict at MI Al Quran Singosari Malang the ware not violation. but discoveret the communication between school hear with in teacher another depply to done to confict in the school.